Republic of Poland : Staff Report for the 2014 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
This 2014 Article IV Consultation highlights that Poland's economy is steadily recovering from the 2012-2013 slowdown on the back of Poland's very strong fundamentals and policies. Real GDP growth moderated to 1.6 percent in 2013 as the slowdown in core euro area countries had knock-on effects on consumer and investor confidence. However, a steady recovery is now under way. The outlook is for a continuing recovery, but external risks remain firmly on the downside. Growth is expected to reach 3.3 percent in 2014 but strong trade and financial linkages with core euro area countries make it vulnerable to growth shocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet